Non-combustible battery solid electrolyte as well as preparation method and application thereof

By using inorganic liquid electrolytes and fluoride -containing organic lithium salt and other materials in lithium ion batteries to agglomerate, to prepare inorganic solid electrolytes, solve the problem of safety hazards of liquid electrolytes in lithium -ion batteries, increase the battery of the battery, and increase the battery. Safety and energy density.

CN119381545APending Publication Date: 2025-01-28WUHAN ZHONGYUAN YANGTZE RIVER TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518098.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The liquid electrolyte in existing lithium-ion batteries has flammable and explosive organic solvents, and the formation of lithium dendrites may lead to short circuits in the battery, leading to safety hazards, excessive temperatures, liquid leakage and other problems.

Method used

The inorganic liquid electrolyte LIALCL4 · 3SO2 and fluorine -containing organic lithium salt, polymerization monomer, and leading agents are prepared to prepare inorganic solid electrolytes through cross -linking agents to ensure that the electrolyte has a high ionic conductivity and inhibit the growth of lithium crystal branches.

Benefits of technology

Effectively suppress the safety hazards brought by the growth of lithium crystal branches, improve the safety and energy density of the battery, and avoid the problem of excessive temperature and leakage liquid caused by liquid electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107272590000061
    Figure BDA0005107272590000061
  • Figure BDA0005107272590000071
    Figure BDA0005107272590000071
  • Figure HDA0005107272600000011
    Figure HDA0005107272600000011
Patent Text Reader

Abstract

The invention discloses a non-combustible battery solid electrolyte, which comprises an inorganic liquid electrolyte LiAlCl4. 3SO2, a fluorine-containing imine organic lithium salt, a polymeric monomer and an initiator, the polymeric monomer accounts for 0.4 wt%-1.2 wt% of the inorganic liquid electrolyte by mass, the initiator accounts for 0.15 wt%-0.25 wt% of the inorganic liquid electrolyte by mass, and the fluorine-containing imine organic lithium salt accounts for 0.5 wt%-1.5 wt% of the inorganic liquid electrolyte by mass. And the fluorine-containing imine organic lithium salt accounts for 0.2 wt%-0.4 wt% of the mass of the inorganic liquid electrolyte. According to the invention, the inorganic solid electrolyte is prepared by adopting the inorganic electrolyte and a cross-linking polymerization method, so that the potential safety hazard caused by the growth of lithium dendrites can be effectively inhibited while the high ionic conductivity of the solid electrolyte is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a non-flammable battery solid electrolyte and a preparation method and application thereof. Background Art

[0002] Since 1999, Sony Corporation of Japan launched the first commercial lithium-ion battery. Over the past few decades, technology has been changing with each passing day. Lithium-ion batteries have developed towards high energy density, high cycle life, and lightweight. With higher requirements for the energy density of lithium-ion batteries, it has greatly promoted the development of electric vehicles and energy storage power stations. However, accidents of lithium-ion battery fires and explosions have also been reported, and safety issues have restricted further development. Therefore, improving the safety of lithium-ion batteries has become the fundamental way to ensure their long-term development and widespread application.

[0003] At present, traditional liquid electrolytes are widely used in lithium-ion batteries, but liquid electrolytes contain flammable organic solvents, and the batteries may have safety problems such as flammable and explosive leakage during use. In the prior art, inorganic liquid electrolyte LiAlCl4·3SO2, as an electrolyte that can be used for lithium metal batteries, has the characteristics of high conductivity, high lithium ion migration number, and non-flammability, and has become one of the effective measures to solve the safety performance of lithium-ion batteries. However, with metallic lithium as the negative electrode of lithium metal batteries, as the battery charge and discharge cycle proceeds, lithium dendrites are easily formed on the surface of metallic lithium, which can easily pierce the diaphragm and cause internal short circuits in the battery. Although inorganic electrolytes are not flammable, the temperature of the battery after the short circuit will rise, which may cause a series of subsequent adverse effects, such as excessive temperature and leakage. When the battery is used in groups, excessive temperature or leakage may cause the batteries, packaging and structural parts around the battery pack to be corroded or damaged, causing the entire battery pack to fail to work or even be scrapped.

[0004] With the development of science and technology, high energy density and high safety requirements are put forward for batteries. Solid-state lithium-ion batteries have high safety, high energy density, long cycle life and high rate performance. Therefore, solid electrolytes are the inevitable trend of lithium-ion battery development. Solid electrolytes replace the diaphragm and electrolyte in liquid batteries with solid electrolytes. On the one hand, the volatile and flammable organic solvents inside the battery are eliminated, reducing the safety problems caused by organic solvents after thermal runaway of the battery. On the other hand, under the same material and the same capacity, the elimination of electrolytes can significantly reduce the weight of the battery and improve the overall energy density of the battery. Since all-solid-state batteries do not have the conduction of liquid electrolytes, the ionic conductivity at room temperature is very low, which limits their scope of application. At present, the so-called "solid-state batteries" on the market still contain a very small amount of liquid organic electrolytes, and they will still catch fire when there are safety problems with the battery. At the same time, these "solid-state batteries" are composed of polymer electrolytes plus a very small amount of liquid organic electrolytes. The internal ionic conductivity of the battery is low, which limits its use.

[0005] CN111490287 discloses a solid electrolyte obtained by in-situ polymerization of a mixed solution including a lithium salt, an organic solvent, an additive and an initiator, wherein the organic solvent includes a base solvent and a functional solvent, the functional solvent is a phosphazene solvent, and the additive is a monomer containing an unsaturated bond; wherein the base solvent includes at least one of carbonate, carboxylate, fluorocarbonate, ether and fluoroether; and includes at least one of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate and vinyl sulfite. However, the technical solution adopts a method of adding a small amount of a functional solvent phosphazene solvent having a flame retardant effect to the existing organic solvent, and the main body is still a volatile and flammable organic solvent, and the phosphazene solvent accounts for only a very small amount. Therefore, in the cross-linking polymerization process, the organic solvent that has not been completely cross-linked and polymerized can burn under battery leakage or open flame conditions, and the safety of the battery cannot be ensured. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a non-flammable battery solid electrolyte in view of the deficiencies in the above-mentioned prior art. The inorganic solid electrolyte is prepared by an inorganic electrolyte and a cross-linking polymerization method. While ensuring that the solid electrolyte has a high ionic conductivity, it can also effectively inhibit the safety hazards caused by the growth of lithium dendrites.

[0007] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0008] A non-flammable battery solid electrolyte comprises an inorganic liquid electrolyte LiAlCl4·3SO2, a fluorine-containing imine organic lithium salt, a polymerized monomer and an initiator, wherein the mass percentage of the polymerized monomer in the inorganic liquid electrolyte is 0.4wt% to 1.2wt%, the mass percentage of the initiator in the inorganic liquid electrolyte is 0.15wt% to 0.25wt%, and the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0wt% to 0.4wt%.

[0009] Furthermore, when the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0, the mass percentage of the polymerized monomer in the inorganic liquid electrolyte is preferably 0.4 wt % to 0.9 wt %.

[0010] Furthermore, when the mass percentage of the fluorinated imine organic lithium salt in the inorganic liquid electrolyte is not 0, the mass percentage of the polymerized monomer in the inorganic liquid electrolyte is 0.4wt% to 1.2wt%, and the mass percentage of the initiator in the inorganic liquid electrolyte is 0.15wt% to 0.25wt%, preferably, the mass percentage of the fluorinated imine organic lithium salt in the inorganic liquid electrolyte is 0.2wt% to 0.4wt%.

[0011] According to the above scheme, the fluorine-containing imine organic lithium salt specifically adopts one or a mixture of any proportion of bistrifluoromethanesulfonyl imide lithium (LiTFSI), bis(fluorosulfonyl) imide lithium (LiFSI), (fluorosulfonyl) (trifluoromethylsulfonyl) imide lithium (LiFTFSI), (fluorosulfonyl) (perfluoro-n-butylsulfonyl) imide lithium (LiFNFSI), etc.

[0012] According to the above scheme, the polymerizable monomer is one of polyethylene glycol diacrylate (PEGDA, molecular weight ≤ 1000), polyethylene glycol acrylate (PEGA, molecular weight ≤ 1000), acrylonitrile (AN), methacrylonitrile, bromoacrylonitrile, etc. Such polymerizable monomers are well compatible with the inorganic liquid electrolyte LiAlCl4·3SO2, ensuring that the inorganic liquid electrolyte, initiator, and polymerizable monomer can be fully mixed before polymerization.

[0013] According to the above scheme, the initiator is an azo initiator, such as azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), etc.; or the initiator is a peroxide initiator, such as benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, etc.

[0014] The present invention also provides a method for preparing the above-mentioned non-flammable battery solid electrolyte, comprising the following steps:

[0015] Step 1, under a protective atmosphere, weighing a polymerization monomer, a fluorine-containing imine organic lithium salt and an inorganic liquid electrolyte, adding them into a transparent glass bottle, wherein the mass percentage of the polymerization monomer in the inorganic liquid electrolyte is 0.4wt% to 1.2wt%, and the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0wt% to 0.4wt%, stirring them evenly with a magnetic force until they are completely dissolved, the stirring temperature is 10 to 35°C, and the stirring time is 1 to 10 hours, to obtain a first mixture;

[0016] Step 2: under a protective atmosphere, adding an initiator to the first mixture, wherein the mass percentage of the initiator to the electrolyte is 0.15wt% to 0.25wt%, and mixing and stirring at a temperature of 10 to 35° C. to obtain a mixed electrolyte;

[0017] Step 3: Place the mixed electrolyte in a constant temperature box at 50-70° C. for 4-16 hours to obtain the non-flammable battery solid electrolyte.

[0018] In the above preparation method, the protective atmosphere is inert gas or nitrogen, and the method can be carried out in a glove box.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts an inorganic electrolyte and a cross-linking polymerization method to prepare an inorganic solid electrolyte. While ensuring high ionic conductivity, it can also effectively inhibit the safety hazards caused by the growth of lithium dendrites, providing an effective solution for the safe use of batteries. The application of the inorganic solid electrolyte can avoid the occurrence of problems such as excessive temperature and leakage caused by the use of liquid electrolytes inside the battery. At the same time, the solid electrolyte has a strong anti-puncture effect, which can effectively inhibit the puncture of lithium dendrites. It has the high safety characteristics of both non-flammable inorganic liquid electrolytes and solid electrolytes, improves its ionic conductivity, electrochemical performance and safety performance, and enables the obtained battery to have higher safety guarantees under higher energy density conditions.

[0021] The inorganic non-combustible battery solid electrolyte of the present invention is composed of an inorganic liquid electrolyte, an initiator and a polymerized monomer, and a fluorine-containing imine organic lithium salt. Within the ratio range required by the present invention, the polymerized monomer can be uniformly mixed with the inorganic electrolyte to ensure the uniformity of the formed polymer electrolyte (i.e., the non-combustible battery solid electrolyte of the present invention). Moreover, the electrodes and electrolytes in the inorganic non-combustible battery solid electrolyte of the present invention are both solid, and they act as electrolytes and diaphragms at the same time, which is convenient for the processing and packaging of the battery, and at the same time, the solid-state battery can use lithium sheets as negative electrodes to obtain higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 and Figure 2 The pictures are respectively the pictures before and after the polymerization reaction of Example 1. DETAILED DESCRIPTION

[0023] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the present invention is not limited to the following embodiments.

[0024] The present invention has no particular limitation on the purity of the raw materials, and analytically pure materials are preferably used, which can be purchased on the market or prepared according to conventional methods known to those skilled in the art.

[0025] In the following embodiments, there is no special limitation on the preparation method of the AC impedance spectroscopy test sample, and any preparation method well known to those skilled in the art can be used; there is no special limitation on the preparation method of the battery, and any preparation method well known to those skilled in the art can be used.

[0026] In the following examples, the protective atmosphere is inert gas or nitrogen and the experiments are carried out in a glove box.

[0027] Example 1

[0028] (1) Electrolyte composition and preparation

[0029] A non-flammable battery solid electrolyte comprises an inorganic liquid electrolyte LiAlCl4·3SO2, a polymerized monomer PEGDA (molecular weight 600, PEGDA described below is all of this molecular weight) and an initiator azobisisobutyronitrile (AIBN), wherein the mass percentage of PEGDA in the inorganic liquid electrolyte is 0.4wt%, and the mass percentage of AIBN in the inorganic liquid electrolyte is 0.2wt%.

[0030] The preparation method of the above-mentioned non-flammable battery solid electrolyte has the following specific steps:

[0031] Step 1, weighing the polymerized monomer PEGDA and the inorganic electrolyte LiAlCl4·3SO2 in a glove box, adding them into a transparent glass bottle, the mass percentage of the polymerized monomer PEGDA to the inorganic electrolyte LiAlCl4·3SO2 being 0.4wt%, stirring them evenly with a magnetic force until they are completely dissolved, the temperature being 25°C, and the stirring time being 6 hours, to obtain a first mixture;

[0032] Step 2: Add initiator AIBN to the first mixture in a glove box, the mass percentage of the initiator to the electrolyte is 0.2wt%, and mix and stir at a temperature of 25° C. to obtain a mixed electrolyte;

[0033] Step 3: Place the mixed electrolyte in a thermostat at 60°C for 10 hours to obtain the non-flammable battery solid electrolyte (labeled as LiAlCl4·3SO2+0.4wt%PEGDA). Figure 1 and Figure 2 As shown, before step three, the electrolyte is a transparent liquid, and after step three, it is converted into a transparent solid electrolyte.

[0034] (2) Preparation of AC impedance spectroscopy test samples and batteries

[0035] The non-flammable battery solid electrolyte prepared in Example 1 was sandwiched between two identical stainless steel sheets and assembled in the positive and negative electrode caps of a button-type battery, and an AC impedance spectrum test was performed.

[0036] The non-flammable battery solid electrolyte prepared in Example 1 was assembled into a button-type half-cell with a Li sheet and a lithium iron phosphate positive electrode sheet.

[0037] Example 2

[0038] The difference between Example 2 and Example 1 is that the 0.4% polymerized monomer PEGDA in Example 1 is changed to 0.8% polymerized monomer PEGDA, and the obtained solid electrolyte is marked as LiAlCl4·3SO2+0.8wt%PEGDA.

[0039] The impedance spectrum test sample and button-type half-cell were prepared in the same manner as in Example 1.

[0040] Example 3

[0041] The only difference between Example 3 and Example 1 is that the 0.4% polymerized monomer PEGDA in Example 1 is changed to 1.2% polymerized monomer PEGDA, and the obtained solid electrolyte is marked as LiAlCl4·3SO2+1.2wt%PEGDA.

[0042] The impedance spectrum test sample and button-type half-cell were prepared in the same manner as in Example 1.

[0043] Example 4

[0044] (1) Electrolyte composition and preparation

[0045] A non-flammable battery solid electrolyte comprises an inorganic liquid electrolyte LiAlCl4·3SO2, LiTFSI, a polymerized monomer PEGDA (molecular weight 600, PEGDA described hereinafter is of this molecular weight) and an initiator AIBN, wherein the mass percentage of LiTFSI in the inorganic liquid electrolyte is 0.3wt%, the mass percentage of PEGDA in the inorganic liquid electrolyte is 0.8wt%, and the mass percentage of AIBN in the inorganic liquid electrolyte is 0.2wt%.

[0046] The preparation method of the above-mentioned non-flammable battery solid electrolyte has the following specific steps:

[0047] Step 1, weighing the polymerized monomer PEGDA, LiTFSI and the inorganic liquid electrolyte LiAlCl4·3SO2 in a glove box, adding them into a transparent glass bottle, the mass percentage of the polymerized monomer PEGDA in the electrolyte LiAlCl4·3SO2 is 0.8wt%, the mass percentage of LiTFSI in the inorganic liquid electrolyte is 0.3wt%, stirring them evenly with magnetic force until they are completely dissolved, the temperature is 25°C, and the stirring time is 6 hours, to obtain a first mixture;

[0048] Step 2, adding initiator AIBN to the first mixture, the mass percentage of the initiator in the electrolyte is 0.2wt%, and mixing and stirring at a temperature of 25°C to obtain a mixed electrolyte;

[0049] Step 3: Place the mixed electrolyte in a thermostat at 60° C. for 10 hours to obtain the non-flammable battery solid electrolyte (labeled as LiAlCl4·3SO2+0.8wt%PEGDA+0.3wt%LiTFSI).

[0050] (2) Battery production

[0051] The impedance spectrum test sample and button-type half-cell were prepared in the same manner as in Example 1.

[0052] Comparative Example 1

[0053] (1) Preparation of electrolyte

[0054] At a temperature of 25°C, a certain mass of tetrachloroaluminate powder is placed in the main container of the reaction device, and SO2 gas is introduced. After about 10 minutes of introduction, most of the solid powder is liquefied. Magnetic stirring is turned on and stirred for 40 minutes to obtain SO2 solvate electrolyte LiAlCl4·3SO2, which is an electrolyte.

[0055] (2) Battery production

[0056] Two identical stainless steel sheets, a diaphragm and the electrolyte were used to make an impedance spectrum test sample, and the electrolyte, Li sheet, lithium iron phosphate positive electrode sheet and diaphragm were assembled into a button cell.

[0057] Comparative Example 2

[0058] The difference between Comparative Example 2 and Example 2 is that the molecular weight of the 0.8% polymerized monomer PEGDA in Example 2 is changed to 2000, and the obtained solid electrolyte is marked as LiAlCl4·3SO2+0.8wt%PEGDA(2000).

[0059] The impedance spectrum test sample and button-type half-cell were prepared in the same manner as in Example 1.

[0060] Comparative Example 3

[0061] The difference between Comparative Example 3 and Example 4 is that the 0.3wt% LiTFSI in Example 4 is replaced by 0.3wt% LiTFSI and 0.3wt% LiF, and the obtained solid electrolyte is marked as LiAlCl4·3SO2+0.8wt% PEGDA+0.3wt% LiTFSI+0.3wt% LiF.

[0062] The impedance spectrum test sample and button-type half-cell were prepared in the same manner as in Example 1.

[0063] Electrical performance test

[0064] The impedance spectrum test samples prepared in the above comparative examples 1-3 and embodiments 1-4 were subjected to performance tests, including ohmic resistance and ionic conductivity. The results are shown in Table 1.

[0065] Table 1 Electrolyte performance test data table

[0066]

[0067] Inorganic solid electrolytes have good thermal stability, high mechanical strength, and are not easy to burn. They have potential application value in extreme environments such as high temperature and high pressure. Comparative Example 1 and Example 1 show that after adding monomer PEGDA to the inorganic electrolyte for thermal polymerization, the ionic conductivity after cross-linking polymerization decreases, mainly because the mobility of ions in the solid electrolyte is limited by the lattice structure, resulting in a slightly lower ion conduction rate. Compared with Example 2, Comparative Example 2 increases the molecular weight of the polymerized monomer PEGDA from 600 to 2000, and its ohmic internal resistance is significantly increased, and the ionic conductivity decreases. The main reason is that PEGDA with a molecular weight of 2000 is solid, and its compatibility with the inorganic electrolyte is poor, resulting in the influence of ion transmission after polymerization.

[0068] Examples 1, 2, and 3 show that as the PEGDA ratio increases from 0.4wt% to 1.2wt%, the ohmic resistance first decreases and then increases. When the PEGDA content is 0.8wt%, the ohmic resistance reaches a minimum value; while the ionic conductivity first increases and then decreases, mainly because PEGDA contains more carbon-oxygen chains, which are flexible. At the same time, the oxygen atoms on the carbon-oxygen chains can promote the transmission of lithium ions. An appropriate amount of PEGDA can improve the lithium ion conductivity of the electrolyte, but too much PEGDA may cause the electrolyte to easily form crystals, resulting in obstruction of the internal ion transmission channel, thereby reducing the conductivity.

[0069] After adding 0.3wt% LiTFSI in Example 4, its ohmic internal resistance is slightly lower than that in Example 2, and its ionic conductivity is also slightly higher than that in Example 2. The main reason is that the fluorine-containing imine organic lithium salt dissolves in the electrolyte, the solubility of lithium ions increases, the amount of ion conduction increases, and thus the ionic conductivity increases. Comparative Example 3 adds a second lithium salt LiF on the basis of Example 4, and its ohmic internal resistance increases and its ionic conductivity decreases. The main reason is that Li in LiF + and F - The combination is stable, but the solubility in the electrolyte is limited, and some electrolytes cannot be completely and evenly dissolved in the electrolyte, which affects the ion transport after polymerization.

[0070] Table 2 Electrolyte performance test data table

[0071]

[0072] From the data in Table 2, it can be seen that the first effect, first discharge specific capacity and cycle performance of the solid electrolyte are slightly lower than those of the liquid electrolyte. Examples 1, 2 and 3 show that as the PEGDA ratio increases from 0.4wt% to 1.2wt%, the first discharge specific capacity and cycle performance first increase and then decrease; Example 4 and Example 2 show that in the solid electrolyte, appropriately increasing the lithium salt that is conducive to ion deintercalation can improve the first discharge specific capacity and cycle performance of the solid electrolyte. From Table 1, it can be seen that when the PEGDA content is 0.8wt%, the ohmic resistance reaches the minimum value and the ionic conductivity reaches the maximum value; the lithium ion concentration in the electrolyte can be increased by increasing the type of lithium salt. In the solid electrolyte, the higher conductivity during the charge and discharge process can effectively transmit lithium ions and reduce the transmission resistance of ions in the electrolyte, thereby improving the performance of the battery. The present invention adds a polymerized monomer to an inorganic electrolyte for thermal polymerization and then polymerizes to prepare a solid electrolyte, and improves the discharge performance of the battery by adjusting the amount of polymerized monomer added and LiTFSI.

[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A non-flammable battery solid electrolyte, characterized in that: The invention comprises an inorganic liquid electrolyte LiAlCl4·3SO2, a fluorine-containing imine organic lithium salt, a polymerized monomer and an initiator, wherein the mass percentage of the polymerized monomer in the inorganic liquid electrolyte is 0.4wt% to 1.2wt%, the mass percentage of the initiator in the inorganic liquid electrolyte is 0.15wt% to 0.25wt%, and the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0wt% to 0.4wt%.

2. A non-flammable battery solid electrolyte according to claim 1, characterized in that: When the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0, the mass percentage of the polymerized monomer in the inorganic liquid electrolyte is 0.4wt%-0.9wt%, and the mass percentage of the initiator in the inorganic liquid electrolyte is 0.15wt%-0.25wt%.

3. A non-flammable battery solid electrolyte according to claim 1, characterized in that: When the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is not 0, the mass percentage of the polymerization monomer in the inorganic liquid electrolyte is 0.4wt% to 1.2wt%, the mass percentage of the initiator in the inorganic liquid electrolyte is 0.15wt% to 0.25wt%, and the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0.2wt% to 0.4wt%.

4. A non-flammable battery solid electrolyte according to claim 1, characterized in that: The fluorine-containing imine organic lithium salt includes one or more of bis(trifluoromethanesulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium, (fluorosulfonyl)(trifluoromethylsulfonyl)imide lithium, (fluorosulfonyl)(pentafluoroethylsulfonyl)imide lithium, and (fluorosulfonyl)(perfluoro-n-butylsulfonyl)imide lithium.

5. A non-flammable battery solid electrolyte according to claim 1, characterized in that: The molecular weight of the polymerizable monomer is less than 1000, and includes one or more of polyethylene glycol diacrylate, polyethylene glycol acrylate, acrylonitrile, methacrylonitrile, and bromoacrylonitrile.

6. A non-flammable battery solid electrolyte according to claim 1, characterized in that: The initiator is an azo initiator or a peroxide initiator.

7. The method for preparing the non-flammable battery solid electrolyte according to claim 1, characterized in that: The steps include: Step 1, under a protective atmosphere, weighing a polymerization monomer, a fluorine-containing imine organic lithium salt and an inorganic liquid electrolyte, adding them into a transparent glass bottle, wherein the mass percentage of the polymerization monomer in the inorganic liquid electrolyte is 0.4wt% to 1.2wt%, and the mass percentage of the fluorine-containing imine organic lithium salt in the inorganic liquid electrolyte is 0wt% to 0.4wt%, stirring them evenly with a magnetic force until they are completely dissolved, the stirring temperature is 10 to 35°C, and the stirring time is 1 to 10 hours, to obtain a first mixture; Step 2: under a protective atmosphere, adding an initiator to the first mixture, wherein the mass percentage of the initiator to the electrolyte is 0.15wt% to 0.25wt%, and mixing and stirring at a temperature of 10 to 35° C. to obtain a mixed electrolyte; Step 3: Place the mixed electrolyte in a constant temperature box at 50-70° C. for 4-16 hours to obtain the non-flammable battery solid electrolyte.

8. The method for preparing the non-flammable battery solid electrolyte according to claim 7, characterized in that: The protective atmosphere is inert gas or nitrogen and is carried out in a glove box.